2010
DOI: 10.1021/jf1039074
|View full text |Cite
|
Sign up to set email alerts
|

Lumichrome and Phenyllactic Acid as Chemical Markers of Thistle (Galactites tomentosa Moench) Honey

Abstract: HPLC-DAD-MS/MS chromatograms of thistle (Galactites tomentosa Moench) unifloral honeys, previously selected by sensory evaluation and melissopalynological analysis, showed high levels of two compounds. One was characterized as phenyllactic acid, a common acid found in honeys, but the other compound was very unusual for honeys. This compound was extracted from honey with ethyl acetate and purified by SPE using C(18), SiOH, and NH(2) phases. Its structure was elucidated on the basis of extensive 1D and 2D NMR ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 20 publications
3
71
0
1
Order By: Relevance
“…Before each injection, the system was stabilized for 10 min with the initial A / B ratio (90:10, v / v ). The injection volume was 10 μl . Quantitative determination of identified compounds was determined based on calibration curves obtained using appropriate standard solutions.…”
Section: Methodsmentioning
confidence: 99%
“…Before each injection, the system was stabilized for 10 min with the initial A / B ratio (90:10, v / v ). The injection volume was 10 μl . Quantitative determination of identified compounds was determined based on calibration curves obtained using appropriate standard solutions.…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, it is the first report of PLA occurred in pickles. It provided a new natural source of PLA in food system, besides the reported source like sourdough (Lavermicocca et al, 2000) and honey (Tuberoso et al, 2010).…”
Section: The Content Of Pla In Chinese Picklesmentioning
confidence: 99%
“…PhLA content in thistle unifloral honey was around 100-800 mg/kg [19] but the high concentrations of PLA were found in heather (820 mg/kg), ling heather (875 mg/kg) and manuka honeys (243 mg/kg) [20]. Very recently, anti-staphylococcal activity against methicillin resistant Staphylococcus aureus was reported in manuka honey which contained high levels of acetic and lactic acids [21].…”
Section: Phla Occurrence and Its Detectionmentioning
confidence: 99%
“…It was found that LAB produced PhLA as a reaction product of amino acid metabolism [22,23]. Its detection by reverse-phase HPLC is simple and widely adopted method for quantitative measurement of PhLA present in fermentation broth [24], honey [19] and rumen fluid [25]. GC/MS and capillary electrophoresis were also used for quantitative measurement of PLA.…”
Section: Phla Occurrence and Its Detectionmentioning
confidence: 99%